On-the-Job E-Learning: Workers’ Attitudes and Perceptions - Batalla-Busquets, Josep-Maria; Pacheco-Bernal, Carmen (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
The use of e-learning for on-the-job training has grown exponentially in the last decade due to it being accepted by people in charge of businesses. Few papers have explored virtual training from the workers’ standpoint, that is, the perception they have about the different training methodologies (face-to-face vs. virtual) and the attitudes they have towards on-the-job learning. Training, in this context, is an investment for both the two participating agents: businesses and workers. It seems logical that knowing the perceptions and attitudes shown by the targets of the training is, at least, as important as knowing the advantages for the companies. To analyse workers’ perceptions and attitudes we conducted an online survey of 2,000 employees of the leading European savings bank, CaixaBank (http://www.caixabank.com/index_en.html), on training habits, perceptions, motivations, and disincentives of undertaking face-to-face or online instruction. The results reveal that workers perceive e-learning as a more flexible and up-to-date training methodology. On the other hand, face-to-face training continues to be perceived as a more motivating methodology compared to virtuality and with better explanations from the course trainers. As regards motivations given by the workers when it comes to training, there are three main groups of attitudes: those which are more affective and social, those which reveal poor adaptability or fear of the new training requirements, and, finally, those linked to the knowledge society. Such results state that while the benefits of distance methodology can be clearly identified from the company’s point of view (i.e., as a flexible and efficient methodology to develop the employees’ skills and knowledge), from the employees’ standpoint, the advantages of virtual training are not so clear and depend to a great extent on their attitude towards the use of virtuality.